Hemangioblastoma: An Uncommon Cause of Polycythemia in a Child - Aryal, Surabhi; Sharma, Arun Kumar (Journal of Nepal Health Research Council, 2024)
Polycythemia is a rare condition in children. Myeloproliferative neoplasms, including polycythemia vera although rare, is an important cause of childhood primary polycythemia. Secondary polycythemia is more common in children due to conditions causing hypoxia or due to pathologic erythropoietin production in malignancies like renal cell carcinoma, Wilms tumor or Hepatocellular carcinoma. Central nervous system hemangioblastoma is one of the rare causes of polycythemia. We report a 13-year-old girl with primarily neurological symptoms identified to be polycythemic during routine evaluation. Clinical examination and neuroimaging subsequently confirmed an intracranial space occupying lesion which was excised. Hemoglobin level normalized after tumor excision. This case report emphasizes the need for thorough systemic evaluation including central nervous system examination in children identified to be polycythemic.Keywords: CNS tumor; hemangioblastoma; polycythemia